Foreign Portfolio Investment Flows and Exchange Rate: Evidence in Indonesia. Issue 2 (26th January 2020) - Anggitawati, Dyah; Ekaputra, Irwan Adi
ABSTRACT: Using unique daily foreign transactions data in both stock and bond markets, we investigate the daily dynamics of the IDR/USD exchange rate and foreign portfolio investment flows. Based on an unrestricted vector autoregression (VAR) model, we find feedback relations between capital market net foreign inflows (NFI) and IDR/USD returns. Further investigation by decomposing capital market NFI into bond market NFI and stock market NFI reveals that only bond market NFI has feedback relations with IDR/USD returns. Meanwhile, we find only a unidirectional relation in the stock market, where stock market NFI does not Granger cause IDR/USD returns, but IDR/USD returns lead stock market NFI. The results suggest that foreign investors tend to rebalance their international portfolio and chase higher returns in the bond market. Additionally, we learn that bond market NFI leads stock market NFI, which means that foreign investments flow to (from) the bond market before they flow to (from) the stock market. Further analysis utilizing dynamic conditional correlation in the bond market confirms the bidirectional relations between NFI and IDR/USD returns. Hence, foreign participation in the bond market appears to yield more impact on the exchange rate than its participation in the stock market.